Fiscal policy in underdeveloped countries : with special reference to India - Chelliah, Raja Jesudoss (London, Allen and Unwin, 1960)
The book attempts to fulfill three main tasks: analysis of the fundamental problems of fiscal policy in underdeveloped countries; delineation of basic structure of public finance; and evaluation of the basic features of Indian tax system and fiscal policies, against the background of planned economic development
Bibliography: p. 162-164.
sju 22/01/2019
Loans
Keywords: Finance, Public; Fiscal policy; Developing countries